Assessing the Moist and Dry Static Energies in the Atmosphere as a Van Der Waals Gas in 2015 and 2017 over the Metropolitan Region of Natal-RN, Brazil - Medeiros, Deusdedit Monteiro; de Mendonça Silva, Isamara; Mendes, David (Anuário do Instituto de Geociências, 2025)
This study evaluated the monthly average of the enthalpy, geopotential, latent heat content, moist static energy, and dry static energy at several levels of the atmosphere as a Van Der Waals gas from radiosonde data at 00:00 UTC and 12:00 UTC over the metropolitan region of Natal-RN-Brazil. The years 2015 and 2017 were considered because they presented more than 70% of complete data, with days coinciding at both times. To construct the vertical profiles of the variables, the density, specific humidity, and geopotential were calculated at each level through a mathematical approximation based on the Calculus. The Van der Waals-like atmosphere results showed that the latent heat content compensated for any change in enthalpy and potential energy from the surface to the mid-troposphere. Energy was exchanged among enthalpy, geopotential, and latent heat content, showing a roughly constant moist static energy. The moist static energy was a conserved quantity under adiabatic and hydrostatic transformations, although the dry static energy was not conserved. The results of the atmosphere as a Van Der Waals gas and the atmosphere as an ideal gas were compared, proving to be similar.